Factors of Information Technology Adoption in Culinary MSMEs in Minahasa - Tangkere, Telly; Polii, Henny J.; Rogahang, Steven S.N (International Journal of Information Technology and Education, 2024)
Adopting information technology (IT) plays an important role in increasing the competitiveness and efficiency of culinary micro, small, and medium enterprises (MSMEs), especially in the Minahasa region, rich in local culinary traditions. This study aims to identify the factors that affect the adoption of IT in culinary MSMEs in Minahasa. A quantitative approach is used by collecting data from MSME owners through surveys designed to explore the technology, organizational, and environmental dimensions. The results of the analysis show that factors such as perception of ease of use, implementation cost, government support, and competitive pressure have a significant influence on IT adoption decisions. The study also found that the level of digital literacy of MSME owners and access to IT infrastructure are key elements that support the adoption process. This research provides insights for policymakers and practitioners in designing relevant and sustainable strategies to increase IT adoption to strengthen the culinary MSME sector in Minahasa